2022
DOI: 10.1038/s41467-022-31574-z
|View full text |Cite
|
Sign up to set email alerts
|

The HHIP-AS1 lncRNA promotes tumorigenicity through stabilization of dynein complex 1 in human SHH-driven tumors

Abstract: Most lncRNAs display species-specific expression patterns suggesting that animal models of cancer may only incompletely recapitulate the regulatory crosstalk between lncRNAs and oncogenic pathways in humans. Among these pathways, Sonic Hedgehog (SHH) signaling is aberrantly activated in several human cancer entities. We unravel that aberrant expression of the primate-specific lncRNA HedgeHog Interacting Protein-AntiSense 1 (HHIP-AS1) is a hallmark of SHH-driven tumors including medulloblastoma and atypical ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 63 publications
2
24
0
Order By: Relevance
“…At the transcriptional level, a possible mechanism is that antisense lncRNAs share a promoter with nearby genes, thereby suffering from similar transcriptional regulation. Bartl and colleagues have reported that lncRNA HHIP-AS1 and HHIP shared promoters, and this promoter activity was negatively regulated by DNA methylation [33]. Herein, we also found that ELF3-AS1 and ELF3 genes shared the same promoter, which makes them both under the repression of SNAI2 and SNAI1 (Fig 9A).…”
Section: Discussionsupporting
confidence: 67%
“…At the transcriptional level, a possible mechanism is that antisense lncRNAs share a promoter with nearby genes, thereby suffering from similar transcriptional regulation. Bartl and colleagues have reported that lncRNA HHIP-AS1 and HHIP shared promoters, and this promoter activity was negatively regulated by DNA methylation [33]. Herein, we also found that ELF3-AS1 and ELF3 genes shared the same promoter, which makes them both under the repression of SNAI2 and SNAI1 (Fig 9A).…”
Section: Discussionsupporting
confidence: 67%
“…This probably happens because HHIP-AS1 is actively transcribed from a SHH-responsive bidirectional promoter shared with the SHH signalling intermediate HHIP. In SHH-driven tumours, the knockdown of HHIP-AS1 induces mitotic spindle deregulation and the consequential reduction of tumorigenicity in vitro and in vivo [ 47 ] . Taken together, these data suggest HHIP-AS1 to be a suitable candidate for further functional studies to explore its possible role in enabling the pro-mitotic effects of SHH pathway activation in childhood T-ALL.…”
Section: Discussionmentioning
confidence: 99%
“…This probably happens because HHIP-AS1 is actively transcribed from a SHHresponsive bidirectional promoter shared with the SHH signalling intermediate HHIP. In SHH-driven tumours, the knockdown of HHIP-AS1 induces mitotic spindle deregulation and the consequential reduction of tumorigenicity in vitro and in vivo (43). Taken together, these data suggest HHIP-AS1 to be a suitable candidate for further functional studies to explore its possible role in enabling the pro-mitotic effects of SHH pathway activation in childhood T-ALL.…”
Section: Discussionmentioning
confidence: 83%